Comparative Study of Haemostatic Agents in Tactical Environments and Their Impact on Survival Time before Evacuation - Kuliś, Aleksandra (Acta medica Lituanica, 2026)
Aim: Uncontrolled external bleeding remains a leading cause of preventable death in military and civilian tactical environments, necessitating continuous improvement in the means and algorithms for haemorrhage control. The aim of this study was to determine the comparative effectiveness and optimal sequence of application of modern methods for controlling external bleeding in tactical medicine, in order to maximise survival of the wounded until evacuation to hospital. Materials and methods: The study was conducted as a systematic review with a semi-quantitative comparison of efficacy and safety based on registries, clinical cohorts, and severe animal models of coagulopathic haemorrhage. Result: The results demonstrated that new-generation chitosan dressings provide 100% survival for up to 180-240 minutes with minimal blood loss (112-300 ml) in models of severe coagulopathy, outperforming kaolin-based standards (86% survival, blood loss 260-1021 ml). The use of any modern topical haemostatic agent in real combat conditions increases survival by 7%, while the systematic introduction of tourniquets and haemostatic agents reduces preventable mortality from extremity bleeding by 67-87%, saving 1,000-2,000 lives in the conflicts in Iraq and Afghanistan alone. Injectable sponges achieve 100% stable haemostasis for up to 72 hours and are applied three times faster than traditional tamponade, which is critically important for deep, narrow wound channels. Early administration of tranexamic acid (within the first three hours) further reduces the risk of death from bleeding by 10-20%. Under the most challenging conditions, the greatest benefit is achieved through the combined use of tourniquets, new-generation chitosan agents, and specialised devices. Conclusions: The proposed differentiated algorithm enables rapid and reliable haemostasis even in cases of deep traumatic coagulopathy and prolonged evacuation, making it a practical tool for updating tactical medicine protocols and significantly improving survival prior to hospital evacuation.